2015
DOI: 10.1016/j.cels.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Neuronal Protein Complexes Reveals Biochemical Activities and Convergent Mechanisms of Action in Autism Spectrum Disorders

Abstract: SUMMARY The prevalence of autism spectrum disorders (ASDs) is rapidly growing, yet its molecular basis is poorly understood. We used a systems approach in which ASD candidate genes were mapped onto the ubiquitous human protein complexes and the resulting complexes were characterized. The studies revealed the role of histone deacetylases (HDAC1/2) in regulating the expression of ASD orthologs in the embryonic mouse brain. Proteome-wide screens for the co-complexed subunits with HDAC1 and six other key ASD prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 45 publications
2
40
1
Order By: Relevance
“…Similar to PSD genes, essential genes have been found to be differentially expressed throughout various stages of development. For example, some essential genes involved in transcriptional regulation are preferentially expressed in early prenatal development (e.g., HDAC1 ; Li et al, 2015) while others play an important role during postnatal development (e.g., FOXP1 ; Bacon et al, 2015). As with PSD genes, this differential expression among essential genes may explain the variability in observed behavioral regression seen in individuals with essential gene mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to PSD genes, essential genes have been found to be differentially expressed throughout various stages of development. For example, some essential genes involved in transcriptional regulation are preferentially expressed in early prenatal development (e.g., HDAC1 ; Li et al, 2015) while others play an important role during postnatal development (e.g., FOXP1 ; Bacon et al, 2015). As with PSD genes, this differential expression among essential genes may explain the variability in observed behavioral regression seen in individuals with essential gene mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, two recent studies from our laboratory integrating genomic, RNA-seq and proteomic data have identified new genes and complexes involved in autism and characterized their function 31,32 . Specifically, analysis of protein–protein interaction networks revealed a module (or coherent community of interacting genes) that was enriched for known genes involved in autism, as well as genes harbouring copy number mutations and rare mutations in autism cases.…”
Section: Genetic Architecture Of Common Diseasementioning
confidence: 99%
“…This module was enriched for genes involved in synaptic transmission, and RNA-seq revealed that many of the genes in a submodule were differentially expressed in the corpus callosum in patients with ASD, providing a putative molecular explanation for the observation that many individuals with ASD have a smaller corpus callosum than controls 32 . Similarly, mapping of rare variants in patients with autism onto protein complexes revealed both novel proteins and novel molecular machinery involved in autism, including the histone deacetylase (HDAC) chromatin remodelling complexes and other protein complexes 31 . Thus, integrating protein interaction data with WGS and WES data can provide new insights into important diseases, including autism, type 2 diabetes 33 and heart disease 34 (additionally reviewed in REF.…”
Section: Genetic Architecture Of Common Diseasementioning
confidence: 99%
“…The protein is part of the large NuRD (nucleosome remodeling and deacetylase) complex, for which also HDAC1/2 are essential components. NurD complex proteins have been associated to autism 43 . Their members, including GATAD2A, display preferential expression in fetal brain development 43 and in recent work has been implicated in SCZ through open chromatin 44 .…”
Section: Dcakdmentioning
confidence: 99%
“…NurD complex proteins have been associated to autism 43 . Their members, including GATAD2A, display preferential expression in fetal brain development 43 and in recent work has been implicated in SCZ through open chromatin 44 . Further, p66a (mouse GATAD2A) was recently shown to 8, 2017; participate in memory preservation through long-lasting histone modification in hippocampal memory-activated neurons 45 .…”
Section: Dcakdmentioning
confidence: 99%